Toward useful services for elderly and people with disabilities 9th international conference on smart homes and health telematics, ICOST 2011, Montreal, Canada, June 20-22, 2011. Proceedings - Abdulrazak, Bess; Giroux, Sylvain; Bouchard, Bruno; Pigot, Hélène; Mokhtari, Mounir (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Smart Homes and Health Telematics, ICOST 2011, held in Montreal, Canada, in June 2011. The 25 revised full papers presented together with  16 short papers and 8 student papers  were carefully reviewed and selected from 94 submissions. The papers are organized in topical sections on smart home and village; health telematics and healthcare technology; wellbeing, ageing friendly and enabling technology; and medical health telematics and healthcare technolo